SKENARIO PENINGKATAN PENDAPATAN DALAM USAHATANI JAGUNG MELALUI ADOPSI TEKNOLOGI DI DESA TULABOLO BARAT, PROVINSI GORONTALO - Tahir, Nur Safitri; Baruwadi, Mahludin; Sirajuddin, Zulham (Lampung University, 2024)
This research aims to examine several scenarios in maize farming by increasing the income generated by maize farming for rural communities in West Tulabolo Village. This increase in income is aimed at through the adoption of advanced agricultural technologies. The research involved interviewing 26 corn farmers using a structured interview guide to assess their current farming practices. The method used in this study is quantitative descriptive data analysis using saturated sampling techniques. The data collected indicates that these farmers have not yet embraced technological advancements, especially when it comes to using hybrid corn cultivation methods like planting a single seed per hole and utilizing organic fertilizers. As a result, these farmers are currently earning low incomes, which amount to Rp. 4.402.090. To maximize profitability, it is crucial to implement improved agricultural methods by integrating technology into the Good Agricultural Practices (GAP) framework. This integration is expected to lead to a significant increase in seasonal revenue, potentially reaching IDR. 19.712.700Keywords: agricultural technology adoption, hybrid corn cultivation, income, maize farming